Mapping the populist mind: A network approach to integrate sociological and psychological models of the populist radical right - Komáromy, Dániel; Rooduijn, Matthijs; Schumacher, Gijs (Frontiers in Political Science, 2024)
Who supports the populist radical right (PRR)? And under what circumstances? We theorize that social status-related envy (SSRE) is the construct that integrates personality- and grievance-based theories of PRR support. To assess our theory, we estimate psychological network models on German survey data to map the complex relationships between PRR support, Big Five personality traits, facets of narcissism, political attitudes, and multiple constructs measuring objective and subjective social status. Our findings confirm previous studies detecting two routes to PRR support: a disagreeable and an authoritarian one. The Bifurcated Model of Status-Deprived Narcissistic Right-Wing Populism claims that SSRE is the distant predictor of PRR support and the two constructs are connected by two pathways. The middle-class route is characterized by disagreeable narcissism (Rivalry) and nativism, while the lower-class route by Neuroticism (potentially Vulnerable Narcissism) and authoritarian right-wing populism. Moreover, we find preliminary support for our expectation that PRR voting is explained by the activation of narcissistic traits by SSRE.